2022
DOI: 10.3390/ani12172241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feed Frequency on Growth, Survival and Behaviour of Juvenile Spiny Lobster (Panulirus ornatus)

Abstract: Spiny lobsters have a range of complex chemical communication pathways that contribute to feeding behaviour. Feed intake is modulated by feed availability and feed characteristics, such as attractiveness and palatability, with behavioural factors, such as social competition and circadian rhythm, providing an extra layer of complexity. In this study, we investigated the effect of feed frequency on survival and growth of early-stage (instar 2–6) juvenile Palunirus ornatus. In addition, we investigated the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Panulirus versicolor exhibited improved carapace length when fed four times, suggesting a recommendation for more night feeding due to its nocturnal behavior [10]. On the other hand, Panulirus ornatus showed increasing growth from one feeding session to sixteen feeding sessions throughout the day [11]. An unresolved issue in our study is the unidentified species of lobster fries, which hinders the analysis of each species' behavior.…”
Section: Fig 3 a Positive Response Of Lobster Fries To The Formulated...mentioning
confidence: 88%
See 1 more Smart Citation
“…Panulirus versicolor exhibited improved carapace length when fed four times, suggesting a recommendation for more night feeding due to its nocturnal behavior [10]. On the other hand, Panulirus ornatus showed increasing growth from one feeding session to sixteen feeding sessions throughout the day [11]. An unresolved issue in our study is the unidentified species of lobster fries, which hinders the analysis of each species' behavior.…”
Section: Fig 3 a Positive Response Of Lobster Fries To The Formulated...mentioning
confidence: 88%
“…In this research, examples of such ingredients include astaxanthin, cholesterol, and MOS (mannan oligosaccharides). Studies have shown that in adult P. ornatus, the highest concentration of astaxanthin and lower concentration of cholesterol result in optimal growth [11]. While these ingredients do not directly affect the growth and survival of P. ornatus in the juvenile stage, their accumulation in the lobster's body can enhance immunocompetence and potentially increase market price [12].…”
Section: Growth and Survivalmentioning
confidence: 99%
“…Future research in feed development for juvenile lobsters should investigate solutions to improve feed intake by prolonging the attractiveness of feeds. Although, utilising multiple feeding frequencies of the feed ration may represent a good strategy to keep feed attractive over time and thus, promote feed intake [25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have seen inter-moult juveniles showing attraction to naïve moulting cues. This may imply an interest in locating the source, as attraction to cues can often correlate with an increase in foraging activity, consumption of exuvia and possibly cannibalism 24 , which is commonly observed in communally housed spiny lobsters 22 , 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%